From Dialogue to Action: Community Recommendations for Inclusive Research Participation Among Underrepresented Populations. - Byiringiro, Samuel; Bellinger, Grace C.; Mezu, Akunna; Wong, Erin; Tomiwa, Tosin; Vazquez, Monica Guerrero; Foster, Adriana; Sheikhattari, Payam; Himmelfarb, Cheryl R.; Miller, Hailey N. (Health Expectations, 2025)
Introduction: Clinical research is a cornerstone to medical innovation, yet Black/African American and Latino populations are underrepresented in clinical research, contributing to poorer health outcomes. Objective: This study examined perspectives on clinical research recruitment and engagement among historically underrepresented populations. Methods: Focus group discussions (FGDs) were conducted with 59 community members and leaders from Baltimore, Maryland, who identified with groups underrepresented in research. Participants were recruited via a research registry, community outreach, and word‐of‐mouth referrals. Each FGD included 8–14 participants and was conducted in English or Spanish. Thematic analysis was applied following a systematic coding process. Results: Participants included 45 (76%) community members and 14 (24%) community leaders, with 44 (75%) identifying as women, 19 (32%) as Hispanic, and 40 (68%) as Black or African American. We identified key barriers to research participation and community‐informed solutions to those barriers including: establishing community relationships to foster trust, sustaining engagement through active and transparent communication, boosting research visibility and awareness through multimodal outreach and messaging, and promoting accessibility with person‐centered accommodations. Further, we demonstrate how the proposed recommendations would help enhance the relevance, rigor, and reach of clinical research projects. Conclusion: Underrepresentation of Black or African American and Latino individuals in research hinders health equity. Findings suggest that researchers should adopt tailored strategies aligned with community needs to foster inclusive engagement. Patient or Public Contribution: The design, implementation, and interpretation of results were informed by a Community Research Council. The research council is part of a larger project which is currently implementing the recommendations from these focus group discussions. Further, research participants received a brief synopsis of the discussion for any additional feedback or comment before implementation of recommendations.